The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10865-017-9850-2
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between marital quality and sleep quality in older adulthood

Abstract: The current study examined how changes in marital quality are associated with changes in sleep quality in older adults over an 8-year period. Older adults from the Health and Retirement Study completed measures of both marital support/strain and sleep quality in 2006, 2010, and 2014 (N = 4981). We used latent growth curve models to examine intraindividual change in support, strain, and sleep quality. Further, we examined interrelationships between changes in each of these three indicators. Results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 68 publications
1
25
1
Order By: Relevance
“…Sleep disturbance was measured as a modified version of the Jenkins sleep scale (Jenkins et al, 1988) that included the following four items: “How often do you have trouble falling asleep?,” “How often do you have trouble with waking up during the night?,” “How often do you have trouble with waking up too early and not being able to fall asleep again?” and “How often do you feel really rested when you wake up in the morning?.” Responses included “Rarely or never,” “Sometimes,” and “Most of the time.” The sleep items were reverse coded, and then, all four items were averaged to create the total score; this approach is consistent with past uses of this scale in the literature (Lee et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Sleep disturbance was measured as a modified version of the Jenkins sleep scale (Jenkins et al, 1988) that included the following four items: “How often do you have trouble falling asleep?,” “How often do you have trouble with waking up during the night?,” “How often do you have trouble with waking up too early and not being able to fall asleep again?” and “How often do you feel really rested when you wake up in the morning?.” Responses included “Rarely or never,” “Sometimes,” and “Most of the time.” The sleep items were reverse coded, and then, all four items were averaged to create the total score; this approach is consistent with past uses of this scale in the literature (Lee et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In other words, people who have a history of engagement in high-quality relationships that can promote social belongingness and emotional security should get better sleep. Although no research to date has tested whether patterns of experiences and behaviors across relationships predict sleep, a sizable body of research has shown that positive aspects of current romantic relationships-such as greater daily self-disclosure (Kane, Slatcher, Reynolds, Repetti, & Robles, 2014), greater perceptions of partner responsiveness (Selcuk, Stanton, Slatcher, & Ong, 2016), greater marital harmony (Prigerson, Maciejewski, & Rosenheck, 1999), and increases in marital quality over time (Lee, Chopik, & Schiamberg, 2017)-all predict better sleep quality and/or duration. Conversely, greater relationship conflict is associated with poorer sleep quality (Hicks & Diamond, 2011), shorter sleep duration (for women), and difficulties falling asleep (El-Sheikh, Kelly, & Rauer, 2013).…”
Section: Romantic Relationships and Sleepmentioning
confidence: 99%
“…Relationship between marriage and health were often analyzed with longitudinal data. For example, longitudinal associations of marital quality and marital dissolution [10], longitudinal associations between depressive symptoms and marital processes [11], longitudinal associations between marital quality and sleep quality in older adulthood [12], and longitudinal associations between alcohol consumption and negative marital quality [13] were investigated. Several longitudinal studies observed bidirectional association between poor marital quality and depression [14], bidirectional association between marital problems and marital dissatisfaction [15], bidirectional associations between changes in insomnia and changes in marital quality [16], and bidirectional relationships between marital and sleep problems [17].…”
Section: Introductionmentioning
confidence: 99%